Effects of field activities by age of 119 emergency response team on the blood pressure, pulse, respiration, and quality of cardiopulmonary resuscitation - Yi, Seungku; Kong, Hasung (Edelweiss Applied Science and Technology, 2024)
This study analyzed the physical changes according to age and the quality of cardiopulmonary resuscitation through experiments by 119 EMT in transporting equipment at the first aid site and performing post-cardiopulmonary resuscitation. In all ages, cardiopulmonary resuscitation was performed without physical load and CPR was performed after moving the equipment, first, the pulse was significantly increased, and the average pulse was measured higher than in other higher age groups under the age of 30. Second, respiratory changes were significantly increased, and average breathing was measured higher than in other higher age groups when CPR was performed after wearing personal protective equipment and moving the equipment. Third, as for changes in blood pressure, all blood pressure rose, and the average blood pressure in the 40s and older was measured higher than that of the younger age. Fourth, in the quality change of cardiopulmonary resuscitation, the pressure rate was found to have a statistically significant difference in those under 30, 30 to 34, and 35 to 39 years of age, and it was measured that the speed was maintained without change in those over 40. Finally, there was a statistically significant difference in pressure depth between those under 30 and those under 35-39 years old, and the average depth was measured deeper than other higher age groups, so it is necessary to develop differentiated education and training methods at those under 30 years of relatively little experience.